1991
DOI: 10.1037/0022-3514.61.3.380
|View full text |Cite
|
Sign up to set email alerts
|

Automatic vigilance: The attention-grabbing power of negative social information.

Abstract: One of the functions of automatic stimulus evaluation is to direct attention toward events that may have undesirable consequences for the perceiver's well-being. To test whether attentional resources are automatically directed away from an attended task to undesirable stimuli, Ss named the colors in which desirable and undesirable traits (e.g., honest, sadistic) appeared. Across 3 experiments, color-naming latencies were consistently longer for undesirable traits but did not differ within the desirable and und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

107
989
18
16

Year Published

1996
1996
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,347 publications
(1,130 citation statements)
references
References 41 publications
107
989
18
16
Order By: Relevance
“…Negative stimuli, such as faces expressing negative emotion, also appear to be a more potent source of involuntary interference to ongoing cognitive tasks than are positive stimuli (Pratto & John, 1991;White, 1996). For example, White (1996) showed that a nonattended, irrelevant angry face interfered with the completion of an ongoing task, whereas a happy face did not disrupt performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Negative stimuli, such as faces expressing negative emotion, also appear to be a more potent source of involuntary interference to ongoing cognitive tasks than are positive stimuli (Pratto & John, 1991;White, 1996). For example, White (1996) showed that a nonattended, irrelevant angry face interfered with the completion of an ongoing task, whereas a happy face did not disrupt performance.…”
Section: Discussionmentioning
confidence: 99%
“…Such guidance of focal attention would be evident if it was demonstrated that some facial expressions lead to more attentionalguidance than do other facial expressions. Given that the rapid recognition of a potential threat or danger would confer an obvious social and biological advantage, it is conceivable that faces expressing negative emotions might be particularly effective at attracting the focus of attention (e.g., Pratto & John, 1991).…”
mentioning
confidence: 99%
“…Specifically, if young infants typically had positive everyday interactions, then their evaluative neutral point, rather than being equidistant from positive and negative evaluations, would shift closer to positive evaluations; this would 7 Some researchers (e.g., Bohner, Bless, Schwarz, & Strack, 1988;Kellermann, 1984) have attempted to rule this out by manipulating the probability and the negativity of events independently and revealing a negativity bias even when the negative and positive events occurred equally frequently (see also Eastwood, Smilek, & Merikle, 2001;Fox et al, 2000;Hansen & Hansen, 1988;Öhman, Lundqvist, & Esteves, 2001;Pratto & John, 1991). Note, however, that if in our daily lives, we do generally experience more positive than negative outcomes, and negative outcomes do therefore stand out, then when faced with an artificial research situation in which there is an equal or higher probability of negative outcomes, we might nevertheless display a negativity bias (Baumeister et al, 2001;Taylor, 1991).…”
Section: A the Negativity Bias In Attention To Emotionsmentioning
confidence: 99%
“…This is because enhanced memories for positive and negative emotional experiences serve an important function for human behaviour (Christianson, 1987). Evolutionarily, stimuli that evoke positive or negative emotional and physiological arousal are more crucial and relevant to human survival than neutral stimuli (Pratto & John, 1991). Thus, it is advantageous to store emotional information as accurately as possible as this leads to a greater probability of survival.…”
Section: Memorymentioning
confidence: 99%
“…Thus, it is advantageous to store emotional information as accurately as possible as this leads to a greater probability of survival. Emotion substantially influences and enhances the vividness and longevity of memories, especially for episodic memory (Pratto & John, 1991). Emotional memory can be defined as "memory for emotional stimuli, events or situations" (van Stegeren, 2008).…”
Section: Memorymentioning
confidence: 99%